Casos y cosas: semanario popular (Vol. 2, No. 68) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: ¡Como a esclavos...!, Rasputin en acción, Ridículos desplantes de un tipejo, La inocencia de las monjas o el niño del nacimiento.

ENGLISH: Includes: slave-like...!, Rasputin in action, Ridiculous rantings of a guy, The innocence of the nuns or the birth child
Cases and things: popular weekly magazine (Vol. 2, No. 68)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas